The Effect of GTAW Welding Current on the Strength of AISI Steel 1045 - Abdul Khair Junaidi; Machdalena Machdalena; Weriono Weriono; Hariman Hariman; Firdaus M (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2022)
Welding is a process of joining materials by melting metal at high temperatures. Gas Tungsten Arc Welding (GTAW) is one of welding method to join metals. This welding process will affect the mechanical properties of a material. So, it is necessary to conduct a study on changes in mechanical properties that occur. This study aims to determine the mechanical properties of AISI 1045 medium carbon steel using the GTAW welding process with a current variation of 80 A and 100 A. The welding was used the AWS EWTh-1 tungsten electrode and ER70S-G filler wire. The type of connection was used a butt weld joint and a single V groove seam with an angle of 60o. The standard of ASTM E8 was used for the manufacture of tensile test specimens. The results of tensile testing with welding current of 80 A was obtained an average stress of 518.463021 N/mm2 and the strain of 19.55%. For welding with a current of 100 A, the average stress was 548.814727 N/mm2 and the strain of 26.44%. Based on the fracture that occurred in the specimen, the critical area for fracture was the Heat Affecting Zone (HAZ), which the area has undergone a phase change during the cooling process. The weld area of connection part in the welding process has higher strength than the HAZ area.